2022
DOI: 10.3390/microorganisms10030650
|View full text |Cite
|
Sign up to set email alerts
|

Organelle Engineering in Yeast: Enhanced Production of Protopanaxadiol through Manipulation of Peroxisome Proliferation in Saccharomyces cerevisiae

Abstract: Isoprenoids, which are natural compounds with diverse structures, possess several biological activities that are beneficial to humans. A major consideration in isoprenoid production in microbial hosts is that the accumulation of biosynthesized isoprenoid within intracellular membranes may impede balanced cell growth, which may consequently reduce the desired yield of the target isoprenoid. As a strategy to overcome this suggested limitation, we selected peroxisome membranes as depots for the additional storage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 63 publications
1
19
0
Order By: Relevance
“…Thus, by improving the tolerance of yeast cells to geraniol and compartmentalizing the geraniol-producing enzymes into peroxisomes, the titer of geraniol was found to increase by 80% [ 72 ]. Similar results were also observed in the protopanaxadiol-producing strain [ 73 ]. Furthermore, using peroxisome targeting sequence 1, the non-carotenogenic yeast Pichia pastoris was able to produce 73.9 mg/L lycopene by targeting heterologous carotene-producing enzymes to peroxisomes [ 74 ].…”
Section: Compartmentalization Strategies For Effective Synthesis Of T...supporting
confidence: 87%
See 1 more Smart Citation
“…Thus, by improving the tolerance of yeast cells to geraniol and compartmentalizing the geraniol-producing enzymes into peroxisomes, the titer of geraniol was found to increase by 80% [ 72 ]. Similar results were also observed in the protopanaxadiol-producing strain [ 73 ]. Furthermore, using peroxisome targeting sequence 1, the non-carotenogenic yeast Pichia pastoris was able to produce 73.9 mg/L lycopene by targeting heterologous carotene-producing enzymes to peroxisomes [ 74 ].…”
Section: Compartmentalization Strategies For Effective Synthesis Of T...supporting
confidence: 87%
“…Furthermore, using peroxisome targeting sequence 1, the non-carotenogenic yeast Pichia pastoris was able to produce 73.9 mg/L lycopene by targeting heterologous carotene-producing enzymes to peroxisomes [ 74 ]. Similar strategies have been used in the biosynthesis of various monoterpenes [ 75 ], sesquiterpenes, including α-humulene [ 76 , 77 ], and triterpenoids, including squalene [ 63 ], β-amyrin [ 78 ], and protopanaxadiol [ 73 ].…”
Section: Compartmentalization Strategies For Effective Synthesis Of T...mentioning
confidence: 99%
“…A possible explanation might be that Ino2p plays a more significant role in phospholipid biosynthesis than Ino4p, and overexpression of INO2 could lead to an imbalance between INO2 expression and its repressor Opi1p, which ultimately leads to activation of the phospholipid biosynthetic pathway of the ER . Alternatively, manipulating the peroxisome proliferation by increasing Pex34p (peroxisome population-regulated protein 34) production while deleting PEX11 (peroxisome population-regulated protein 11) and ATG36 (autophagy-related protein-encoding gene) improved PPD production by 78% (4 mg/L) compared to the original yeast strain . These results indicate that ER size and peroxisome proliferation likely influence PPD production, although the rational for the latter is rather unclear.…”
Section: Metabolic Engineering Of Yeast For Ppd Synthesismentioning
confidence: 99%
“…50 Alternatively, manipulating the peroxisome proliferation by increasing Pex34p (peroxisome population-regulated protein 34) production while deleting PEX11 (peroxisome populationregulated protein 11) and ATG36 (autophagy-related proteinencoding gene) improved PPD production by 78% (4 mg/L) compared to the original yeast strain. 51 These results indicate that ER size and peroxisome proliferation likely influence PPD production, although the rational for the latter is rather unclear.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Indeed, Artuso et al [ 14 ] proposed that Aminobacter species could be exploited in bioaugmentation and bioremediation processes, while Gammuto et al [ 13 ] suggested a possible development of new tools based on the use of P. aeruginosa azurin p28 domain for treating cancer diseases. Finally, in another work comprised in this Special Issue, Choi et al [ 19 ] engineered the yeast Saccharomyces cerevisiae by modifying the expression of three peroxisome proliferation-related proteins: the obtained mutant strains had an increased amount of peroxisomes and/or enlarged peroxisomes that provided additional storage space for the accumulation of protopanaxadiol synthesized through the expression of heterologous biosynthetic genes.…”
mentioning
confidence: 99%